Zoantharians (Hexacorallia: Zoantharia) Associated with Cold-Water Corals in the Azores Region: New Species and Associations in the Deep Sea - Carreiro-Silva, Marina; Ocaña, Oscar; Stanković, David; Sampaio, Íris; Porteiro, Filipe M.; Fabri, Marie-Claire; Stefanni, Sergio (Frontiers in Marine Science, 2017)
Zoantharians are a group of cnidarians that are often found in association with marine invertebrates, including corals, in shallow and deep-sea environments. However, little is known about deep-sea zoantharian taxonomy, specificity and nature of their associations with their coral hosts. In this study, analyses of molecular data (mtDNA COI, 16S and 12S rDNA) coupled with ecological and morphological characteristics were used to examine zoantharian specimens associated with cold-water corals at depths between 110 and 800 m from seamounts and island slopes in the Azores region. The zoantharians examined were found living in association with stylasterids, antipatharians and octocorals. From the collected specimens, four new species were identified: (1) Epizoanthus martinsae sp. n. associated with the antipatharian Leiopathes sp.; (2) Parazoanthus aliceae sp. n. associated with the stylasterid Errina dabneyi (Pourtalès, 1871); (3) Zibrowius alberti sp. n. associated with octocorals of the family Primnoidae (Paracalyptrophora josephinae (Lindström, 1877)) and the family Plexauridae (Dentomuricea aff. meteor Grasshoff, 1977); (4) Hurlizoanthus hirondelleae sp. n. associated with the primnoid octocoral Candidella imbricata (Johnson, 1862). In addition, based on newly collected material, morphological and molecular data and phylogenic reconstruction, the zoantharian Isozoanthus primnoidus Carreiro-Silva, Braga-Henriques, Sampaio, de Matos, Porteiro & Ocaña, 2011, associated with the primnoid octocoral Callogorgia verticillata (Pallas, 1766), was reclassified of as Zibrowius primnoidus comb. nov. The zoantharians, Z. primnoidus comb. nov., Z. alberti sp. n. and H. hirondelleae sp. n. associated with octocorals showed evidence of a parasitic relationship, where the zoantharian progressively eliminates gorgonian tissue and uses the gorgonian axis for structure and support, and coral sclerites for protection. In contrast, the zoantharian P. aliceae sp. n. associated with the stylasterid E. dabneyi and the zoantharian E. martinsae sp. n. associated with the antipatharian Leiopathes sp., appear to use the coral host only as support with no visible damage to the host. The monophyly of octocoral-associated zoantharians suggests that substrate specificity is tightly linked to the evolution of zoantharians.